AGE-RELATED LEFT VENTRICLE MYOCARDIAL REMODELING: IS THERE A LINK WITH NORMAL AGEING? - E. V. Plokhova; D. U. Akasheva; O. N. Tkacheva; I. D. Strazhesko; E. N. Dudinskaya; A. S. Kruglikova; M. V. Agaltsov; V. S. Pykhtina; N. V. Sharashkina; N. V. Brailova; D. A. Skvortsov; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To study the age-related changes in structure of myocardium of the left ventricle and their relation with telomere length. With the age even in absence of cardiovascular diseases (CVD) and risk factors (CRF) there is a changing of the left ventricle (LV) myocardium structure. Probable mechanism of the age-related changes is cell ageing. One of the markers of cell ageing is telomere length (TL) that is also a marker of biological age. Material and methods. After screening we included 303 persons at the age 23-91 y.o. without clinical signs of CVD. All participants underwent transthoracal echocardiography by the standard method. Telomere length was measured in leucocytes on the genomic desoxyribonucleic acid (DNA) by real-time polymerase chain reaction method (PCR). We measured the relative length of telomeres. For the assessment of parameters relations we used correlational logistic regression analysis and build-up of multidimensional regression models. Results. Older age group (women >55 years and men >45 years) of those without significant signs of CVD and CRF comparing to the group of younger persons we found thicker LV myocardium and its concentric remodeling. TL was significantly linked with the age (β=-0,012, p=0,0001). Also we found the relation of TL with LV structure parameters: interventricular septum thickness (IVST) (β=-0,028, p=0,01), relative wall thickness (RVT) (β=-0,012, p=0,02) using the age and CRF. However shorter telomeres (<9,75 units) were not related to the increase of IVST (OR=1,44; 95% CI 0,84-2,47; p=0,18), posterior wall thickness (PWT) (OR=1,56; 95% CI 0,37-6,59; p=0,55) and RVT (HR=1,40; 95% CI 0,74-2,65; p=0,31). Conclusion. Left ventricle hypertrophy and its concentric remodeling in older age group without CVD and CRF shall be regarded as age-related. LT, cell ageing marker, is not related to the age-specific changes of LV structure.